The OFDI policy path and the product space - Matthew Stephenson (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2021)
Outward FDI policy can be understood as progressing down a path that informs the growing selection of home-country measures (HCMs), which can be used to both leverage existing and develop new capacity. The Product Space can help select HCMs to target goods and services that are slightly more complex, thus helping to drive home-economy upgrading.
Keywords: 330